A modified Delphi consensus on generic indicators for a low‐ and middle‐income country's quality nursing care measurement - Chijioke O. Nwodoh; Ijeoma L. Okoronkwo; Agnes N. Anarado; Ada C. Nwaneri; Anthonia U. Chinweuba; Ifeoma Ndubuisi; Peace Iheanacho; Nneka Ubochi; Echezona Nelson D. Ekechukwu (Wiley, 2022)
Abstract Aim This study aimed to develop generic quality nursing care indicators for a low‐ and middle‐income country's quality nursing care measurement through a modified Delphi consensus. Design A three‐round modified Delphi process guided the items' development and acceptance consensus. Methods Twenty‐four academic and clinical nursing experts from different parts of Nigeria participated in the Delphi rounds. In the first round, 96 items (structure - 31, process - 38, and outcome - 27) were distributed to the panellists through e‐mail. The same method guided round 2. In round 3, the panellists reached a consensus on the number and structure of the items. Results In round 1, the initial items were reduced to 75 that met the Delphi consensus. In round 2, the items were modified further and reduced to 74. In round 3, the experts reached a consensus on 70 items (structure - 28, process - 32, and outcome - 10).